Grodeliveryo: Mobile Application for Grocery, Purchasing and Delivery - Kaliappen, Kugenthiren; Aman, Hannani (Applied Information Technology And Computer Science, 2022)
Grodeliveryo: Mobile Application for Grocery, Purchasing and Delivery is an application that connects a staff of the store and his customers. Valli Store is a grocery store which selling groceries with their traditional process, where the purchase needs to be made on there with cash only. Also, the store stock management are not handling systematically. The stock needs to buy are written on paper for the store purchase to their dealer. The system provides seven modules including login, registration, manage groceries, cart, notification, feedback and generate report. This project is based on a mobile based application, so Unity and Visual Studio Code is used to develop the application. This project was implemented using the SDLC model. The development of this system will enable efficient grocery management and delivery management for deliver grocery orders. All the testing for the developed application has been tested successfully. Finally, Grodeliveryo managed to help the staff runs groceries efficiently and customer can also buy and track their purchases efficiently.